PENGARUH PERUBAHAN TARIF PAJAK, KEBIJAKAN KEMITRAAN, DAN REGULASI PENDANAAN BAGI UMKM TERHADAP MINAT BERWIRAUSAHA - Andri Waskita Aji; Yudi Ausah (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the effect of changes in tax rates.partnership policies and funding regulations for MSMEs on interestentrepreneurship at the students of the Faculty of Economics, University of Sarjanawiyata Tamansiswa. This research method uses a quantitative descriptive method from primary data by using a questionnaire. Directly from the study obtained a sample of 100 respondents from active students of the Faculty of Economics consisting of the Accounting and Management Study program The results of this study indicate that funding regulations for MSMEs has a positive effect on  entrepreneurial interest in students of the Faculty of Economics, Bachelorwivata Tamansiswa University, while changes in tax rates and tax rates partnership policy does not have a positive effect on entrepreneurial interest in students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa